The Best Partner for the Family Review of Takhrīj al-Ḥadīṡ “Khiyārukum Khiyārukum Linisāihim” in the Book of Sunan Al-Tirmiżī - Nur Mazaya Hurin In; Mohammad Ikhwanuddin; Salman Al Farisi; Thoat Stiawan; Gàndhung Fajar Panjalu (Al Qalam: Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2026)
In the Islamic context, the quality of the relationship between husband and wife is greatly influenced by the husband's character, which is measured based on the hadith "Khiyārukum Khiyārukum Linisāihim," narrated in the Sunan al-Tirmidhi. This study aims to analyze the normative meaning of this hadith, particularly in relation to the husband's character within the family. The research methodology employed is qualitative, using a library research approach and the Takhrīj al-Ḥadīṡ technique to verify the sanad and matn of the hadith, along with a syarah analysis to understand the relevance of the hadith's content to the husband's character in building a sakinah family. The findings of this study indicate that the quality of a husband's faith is reflected in his treatment of his wife, which includes love, justice, responsibility, and gentleness. This discovery contributes to understanding the importance of the husband's character in creating marital harmony and reducing the potential for divorce. In conclusion, this research affirms that this hadith is not only theologically relevant but also practical in establishing a sakinah, mawaddah, and rahmah Islamic family. Future research is expected to further explore the application of the values in this hadith within the context of modern social realities.